(3GdeWhd aj GdbGfhf GdeOfjs (3eaGYjd GdYbO Gh GKGQgs - (3ZSJGf(B, (3LGcs; (3Hjhs; (3LGeGfs ((3HjQhJs (3GdeDSSg GdLGeYjg ddOQGSGJ hGdfTQ hGdJhRjYs, 2000)
(3jYQV GdcJGH GjVG GdbGfhf GdPj jShS eaGYjd GdYbO, JLGg GdaQbGA (B((3JaSjQ GdYbO hhUag heOJg(B) (3hJLGg GdZjQ (B((3GdMLjI hGdYdfjI GdbGfhfjI hGdZT GdHhdjGfj, Ch GdHhdUj, hGdUhQjI, hGdJeKjd, hGdGTJQGW dUGdM GdZjQ, hGdJfGRd Yf GdYbO, hGdOYhi GdeHGTQI(B). (3hgh jbOe fXQjI YUQjI ddYbO eHfjI Ydi JMdjd eYeb ddabg hddbGfhf GdhVYj, hYdi hLg GdNUhU dGLJgGO eMceI GdfbV (B((3Ch eMceI GdJejjR aj dHfGf(B). (3Efg JJeI Jchjf GdYbO aj GdeWqhd aj GdbGfhf GdeOfj(B. (3hde JJa gPg GdWHYI HeLQO GdJfbjM(B. (3EfgG JLfj aGFOI GdfbGT Gdabgj GdPj fei MOjKkG aj TCf GdJaQjb Hjf GdaQbGA hGdZjQ dJbOje eYjGQ LOjO hJUfja LOjO eSJfJLjf ef Pdc(B. (3hgj JHSW GdfJGFL, hdG SjeG aj eG jJYdb HGdfXGe hGdehba GdefGSH aj TCf GdJfGRd GdGJaGbj GdeaJQV Yf GdYbO(B. (3hgj JMOO HObI GdQhGHW GdJj JhMO GdOYGhi GdeHGTQI heLehYGJ GdYbhO(B.s
Keywords: (3GdYbhOs; (3GdbGfhf GdeOfjs